Factors affecting investor satisfaction in the southeast economic zone of Nghe An province - Mai, Le Vu Sao; Kopsack, Dalasouk; Tieng, Nguyen Thi; Trang, Hoang Thi Huyen; Khoa, Tran Dang (Asian Economic and Financial Review, 2023)
This study looks at the factors affecting investor satisfaction in the economic zone of Nghe An province, Vietnam, by building a regression model to measure the impact of the factors and propose solutions to increase investment attractiveness. The exploratory factor analysis (EFA) method is used for empirical research. The results showed that there are six factors affecting investor satisfaction. In order of influence, these are incentives, habitat, local organizations, geographical location, infrastructure, and human resources. From this result, we propose creating favorable policies to support disadvantaged businesses, creating favorable conditions for businesses to borrow capital, improving social infrastructure to attract workers, strengthening business support, focusing on the seaport system, and taking advantage of all available resources.